Post-Traumatic Growth pada Wanita Dewasa Madya Pasca Mastektomi - Najlina Sofy Azzahra; Ellyana Ilsan Eka Putri (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This study aims to determine the factors and processes of post-traumatic growth in post-mastectomy middle-aged women. Post-traumatic growth is a person's psychological change towards a positive direction that indicates a person has gone through a struggle through a trauma in his life that is challenging and psychologically stressful. The method used in this research is qualitative phenomenology. The technique used to collect data in this research is In-Depth Interview and analyzed using the interpretative phenomenological analysis (IPA) approach. The results found in this study have main themes, namely factors and processes related to post-traumatic growth. The factors that make informants able to achieve post-traumatic growth are social support from family and environment, spirituality, and optimism. The process that informants go through in achieving post-traumatic growth is through the stages of rumination style, distress management, emotional disclosure, coping strategies and social support to achieve post-traumatic growth.